Possibility of Using Flexible Dentures over Iliac Bone Graft in Adolescent Patients with Ameloblastoma: A 9-Month Follow-Up Clinical Report - Ammar Belal; Bassil Monther; Wael Alzarif (Hindawi Limited, 2021)
Introduction. The use of bone grafts is a common procedure after excision and reconstruction of the mandible, although it is rare in children and adolescents due to incomplete growth, which means a long transition period until reaching an appropriate age for implants or more predictable outcomes. Case Report. This article describes a 9-month follow-up of the use of a flexible denture above a bone graft taken from the anterior iliac crest for adolescent patients with resected mandible due to ameloblastoma. Taking into account prosthetic considerations, radiography, and clinical observation, no complications were seen with the graft. Conclusion. It is safe to use a flexible denture as a prosthetic over an iliac bone graft block during the healing period.